PENGARUH PENGEMBANGAN KARIR DAN KOMPETENSI TERHADAP EFEKTIVITAS KERJA KARYAWAN PT LOGIKREASI UTAMA MEDAN - Jessi Jessi; Imanuel Tarigan; Syawaluddin Syawaluddin (STIE-PMCI, 2020)
Abstract.This research was conducted at PT Logikreasi Utama Medan. The purpose of this study was to determine and analyze the effect of Career Development and Competence on the Work Effectiveness of the employees of PT Logikreasi Utama Medan. The population numbered 35 employees while the sample in this study were: 35 employees. The sampling technique used is saturation sampling. Data collection techniques are the distribution of questionnaires, interviews and documentation studies. Data analysis uses multiple linear regression analysis.The conclusion of the study is that simultaneously Career and Competency Development influences the Work Effectiveness of the employees of PT Logikreasi Utama Medan. Partially, Career Development influences the Work Effectiveness of the employees of PT Logikreasi Utama Medan. Partially, Competence influences the Work Effectiveness of employees of PT Logikreasi Utama Medan. The magnitude of the coefficient of determination seen from Adjusted R Square is: equal to 0.430 means Career Development and Work Competence can explain Employee Work Effectiveness of 43% and the remaining 57% is influenced by other variables outside of this study such as: Job Placement, Job Training, Job Promotion and so.Â Â Keywords: Career Development, Competence, Work Effectivene